The millipede genus Anaulaciulus Pocock, 1895 in Taiwan, with descriptions of four new species (Diplopoda, Julida, Julidae) - Mikhaljova, Elena V.; Golovatch, Sergei I.; Chang, Hsueh-Wen (Zootaxa, 2011)
The genus Anaulaciulus Pocock, 1895 is represented in Taiwan by eight nominate species, all keyed and nearly all mapped, including four new ones: A. immensus sp. nov., A. oligosegmentatus sp. nov., A. multiarticulatus sp. nov. and A. setulifer sp. nov. One species, A. tonginus (Karsch, 1881), is confirmed to be present in the fauna of the island, while the remaining three require revision. Taxonomic and distributional remarks are provided for all of the species.